An emerging framework for fully incorporating public involvement (PI) into patient-reported outcome measures (PROMs) - J. Carlton; T. Peasgood; S. Khan; R. Barber; J. Bostock; A. D. Keetharuth (Journal of Patient-Reported Outcomes, 2020)
Abstract Patient-reported outcome measures (PROMs) are widely used in the United Kingdom (UK) and internationally to report and monitor patients’ subjective assessments of their symptoms and functional status and also their quality of life. Whilst the importance of involving the public in PROM development to increase the quality of the developed PROM has been highlighted this practice is not widespread. There is a lack of guidance on how public involvement (PI) could be embedded in the development of PROMs, where the roles can be more complex than in other types of research. This paper provides a timely review and sets out an emerging framework for fully incorporating PI into PROM development.